2014
DOI: 10.1021/ef5021186
|View full text |Cite
|
Sign up to set email alerts
|

Exposures to Carbon Monoxide from Off-Gassing of Bulk Stored Wood Pellets

Abstract: There has been a significant increase in use of wood pellets in residential and commercial scale boiler systems within New York State, such an increase will lead to increased storage of bulk pellets in homes and buildings. Serious accidents in Europe have been reported over the past decade in which high concentrations of carbon monoxide (CO) have been found in bulk pellet storage bins. Thus, additional exposure data for CO in pellet bin storage areas are needed to assess the potential hazards. Using calibrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 7 publications
3
33
1
Order By: Relevance
“…In general, the pellet samples were ~6 mm in diameter and 6–25 mm in length with a bulk density of ~18 kg/m 3 (40 lbs/ft 3 ). For more details, refer to Soto-García et al 3 …”
Section: Experimental Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the pellet samples were ~6 mm in diameter and 6–25 mm in length with a bulk density of ~18 kg/m 3 (40 lbs/ft 3 ). For more details, refer to Soto-García et al 3 …”
Section: Experimental Systemmentioning
confidence: 99%
“…Thus, it is important to understand their potential health impacts to building occupants. While immediate health concern with wood pellet storage is the off-gassing of carbon monoxide (CO), 3 another concern is the adverse impact of indoor air quality due to the off-gassing of volatile organic compounds (VOCs) from storage of wood pellets. 4–6 VOCs constitute a significant class of indoor air contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,18,19 Gauthier et al 20 documented several deaths arising from CO poisoning in large pellet storage areas and reviewed previously reported incidents in marine vessels and commercial and residential pellet and chip storage facilities in Europe. The illness and deaths associated with pellet storage clearly demonstrate risk to human health and the need to fully understand the emission rates and concentrations of CO. SotoGarcia et al 9 showed elevated CO concentrations in a variety of storage facilities but did not observe values in the range of the extremely high values reported by Gautier et al 20 To characterize the off-gassing rate for softwood pellets, Kuang et al 7 developed a kinetic model of CO, CO 2 , and CH 4 emissions from British Colombia pellets (widely used in Europe) made from Pinus sylvestris (Scots pine). This model assumes that the gas formation reaction is first-order because their results showed that the gas concentrations initially increased exponentially over time and then tended to a constant plateau after a few days.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The topic has been investigated in several recent publications, e.g. [6,7] but the exact nature of the chemical processes at play do still not appear to be well-understood.…”
Section: Wood Pellet Chemical Off-gassing Risksmentioning
confidence: 99%